The Long Revolution of Radiocarbon as Seen through the History of Swiss Lake-Dwelling Research - Delley, Géraldine (My University, 2015)
This paper reassesses the implementation of radiocarbon dating in archaeology based on the technique’s development while researching ancient lake dwellings in Switzerland between 1950 and 1970. The aim is to explain archaeologists’initial failure to accept the results obtained by this method. Two key issues are thereby the core focus of this analysis. The first concerns the disciplinary context that influenced the reception of 14C dating among prehistorians. The second deals with methodological discussions concerning 14C dating and dendrochronology, being radiocarbon dating’s most related chronological tool. While dendrochronology and 14C were first complementary in the 14C calibration process since the 1960s, it was then quickly realized that dendrochronology produced more detailed temporal data due to the good preservation conditions of wooden structures at Swiss lake dwellings and thus competed with 14C results. In fact, this competition had to do with the two differing methodologies of data acquisition and time measurement.
Keywords: History of science; 1950-1980; Radiocarbon; Dendrochronology; Swiss lake-dwelling research